Observation of the decay B s 0 → K 0 p p ¯ $$ B_s^0→ K^0p\overline{p} $$ and measurement of the B s 0 → K 0 p p ¯ $$ B_{(s)}^0→ K^0p\overline{p} $$ branching fractions - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics)
Abstract A study of the charmless baryonic decays B s 0 → K 0 p p ¯ $$ B_{(s)}^0→ K^0p\overline{p} $$ is presented, where B s 0 $$ B_{(s)}^0 $$ denotes either a B 0 or a B s 0 $$ B_s^0 $$ meson. The analysis is based on proton-proton collision data collected by the LHCb experiment at centre-of-mass energies of 7, 8, and 13 TeV, corresponding to an integrated luminosity of 9 fb −1. The decay B s 0 → K 0 p p ¯ $$ B_s^0→ K^0p\overline{p} $$ is observed for the first time, with a measured branching fraction of (9.14 ± 1.69 ± 0.90 ± 0.33 ± 0.20) × 10 −7 and a significance of 5.6σ. The uncertainties respectively account for statistical and systematic contributions, the precision of the branching fraction of the normalisation channel B 0 → K 0 π + π − and the fragmentation fraction ratio f s /f d . The branching fraction determined for B 0 → K 0 p p ¯ $$ B^0→ K^0p\overline{p} $$ is (2.82 ± 0.08 ± 0.12 ± 0.10) × 10 −6, which is the most precise measurement to date.